Magnetic to non-magnetic transition of Ce induced by volume in Ce(Pd, Ni) and electron concentration in Ce(Pd, Rh) - Kappler, J.P. (1988)
Fil: Nieva, G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina